The Role of Scheme Method to Improve the Ability in Solving Mathematical Word Problems - Murtini, Dian Kinayung (Universitas Ahmad Dahlan, 2013)
Abstract Â Solving mathematical word problems are not easy for elementary school students. Third-grade students of elementary schools cannot understand mathematical word problems perfectly. The appropriate learning method is needed to improve the studentsâ ability in understanding to solve the questions. Therefore, the objective of this study is to identify the role of the scheme learning method to improve studentsâ ability in solving mathematical word problems. Third-grade students of elementary school took the process of this research. The students were divided into two groups; experimental and control groups. This research would be carried out in three sessions. The measurement of the studentsâ ability in solving the mathematical word problems was conducted by giving the pre-test and post-test mathematics materials. Data analysis performed used anava mixed design to compare score of studentsâ abilities in solving the mathematical word problems between experimental and control groups. The result of this study indicated that there were differences in score of studentsâ abilities in solving the mathematical word problems between experimental group and control group (p=0,039, p<0,05).Â Students who received scheme learning method increased their score more than control group. Applying this method can improved studentsâ ability in solving mathematical word problems.Â Keywords: scheme learning method, mathematical word problems, ability in solving mathematical word problems.Â